Buckling Pneumatic Linear Actuators Inspired by Muscle. Issue 3 (1st June 2016) - Yang, Dian; Verma, Mohit S.; So, Ju‐Hee; Mosadegh, Bobak; Keplinger, Christoph; Lee, Benjamin; Khashai, Fatemeh; Lossner, Elton; Suo, Zhigang; Whitesides, George M.
Abstract : The mechanical features of biological muscles are difficult to reproduce completely in synthetic systems. A new class of soft pneumatic structures (vacuum‐actuated muscle‐inspired pneumatic structures) is described that combines actuation by negative pressure (vacuum), with cooperative buckling of beams fabricated in a slab of elastomer, to achieve motion and demonstrate many features that are similar to that of mammalian muscle.